Anthropometrics and fitness components profiles of division one IPT league soccer players / Mohd Faridz Haji Ahmad - Haji Ahmad, Mohd Faridz (2013)
Soccer is the most popular sports in the world and its popularity continues to increase in Malaysia. Hence, “Liga Institusi Pengajian Tinggi” or IPT League had been introduced to select potential players. In soccer, having great fitness components contributes to better performance with the additional of anthropometries characteristics. Therefore, the aim of this study was to investigate the anthropometries and fitness components differences among team in Division One IPT League 2012. There were 160 participants (N=160), consisting of players from Universiti Teknologi MARA (UiTM); Universiti Malaya (UM); Universiti Kebangsaan Malaysia (UKM); Kolej Komuniti Kedah (KKK); Politeknik Kota Bharu (PKB); Universiti Multimedia (MMU); Universiti Tun Hussein Onn (UTHM) and Universiti Malaysia Sabah (UMS), where each team contributes 20 players. The age of these participants ranged between 18 to 25 years old. The participant’s anthropometries characteristics that were measured were height, weight and body fat percentage. For fitness level, T-test had been used to measured agility, sit and reach (flexibility), vertical jump (power), 30m sprint (speed), sits ups test (strength) and Yo-Yo Intermittent Recovery Test- Level 1 (VChmax). Results showed that there are significant differences in weight (p = .04) and body fat percentage (p = .03) while it showed no significant differences in height (p = .28), agility (p = .07), flexibility (p = .97), power (p = .81), speed (p = .78), strength (p = .92) and cardiovascular endurance {p = .10). In conclusion, teams in IPT League 2012 shared almost similar height and fitness level but having differences in term of weight and body fat percentage. These findings contributed to sports management, the body of knowledge especially for coaches to make decisions in selecting players and emphasizing on other factors rather than tested fitness components as in the study.